Management of the Nahdlatul Wathan Lombok Qur'an Home Education Strategy in Creating Qur'anic Generations - Lalu Gede Muhammad Zainuddin Atsani; Ulyan Nasri; Muzakkir Walad; Nurdiah Nurdiah (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This research aims to discover the educational management strategy of Rumah Qur'an NW Lombok in printing the Qur'anic generation. This study uses a qualitative approach, while the method used in this research is descriptive with observation techniques, interviews and documentation studies. The data analysis used is the analytical technique offered by Miles and Huberman namely Data Collection, Data Reduction, Data display and data verification or drawing conclusions. The results of this study are: First, the educational management strategy of Pondok Tahfidz Baqiyatussalaf NW—Rumah Qur'an Nahdlatul Wathan Lombok in producing Qur'ani generations, namely by making planning (planning) which includes issues of curriculum development strategy, activity development strategy, strategy Boarding School, Social Media Utilization Strategy, Funding Strategy. Second, implementing the management of Pondok Tahfidz Baqiyatussalaf NW - Rumah Qur'an Nahdlatul Wathan Lombok in creating the Organizing stage of the Qur'ani generation by actualizing five excellent programs namely the I'dad Program, the Tahfidz Program, the Tasri' Program, the Mutqin Program, and the Takmili Program. Third, the implications of the management of Pondok Tahfidz Baqiyatussalaf NW—Nahdlatul Wathan Lombok Qur'an House in creating the Qur'ani generation are divided into three, namely; Academic Implications, Spiritual Implications, and Social Ethical Implications. The contribution of this research to students is as an alternative to anticipating juvenile delinquency, the negative influence of technology and a social environment that is not conducive. So, Pondok Tahfidz Baqiyatussalaf NW — Rumah Qur'an Nahdlatul Wathan Lombok is an alternative solution.